Reversible planar gliding and microcracking in a single-crystalline Ni-rich cathode - Bi, Yujing; Tao, Jinhui; Wu, Yuqin; Li, Linze; Xu, Yaobin; Hu, Enyuan; Wu, Bingbin; Hu, Jiangtao; Wang, Chongmin; Zhang, Ji-Guang; Qi, Yue; Xiao, Jie (Science (American Association for the Advancement of Science), 2020)
Polycrystalline cathode materials that contain a combination of nickel, manganese, and cobalt have been used for advanced lithium batteries. These materials fracture at high voltage, which increases surface area and leads to more side reactions and shorter cycle life. Using single-crystalline samples as model materials, Bi et al. observed changes in nickel-rich cathodes to study the fracture behavior under well-characterized conditions. As the material is charged and lithium is removed, specific planes glide over one another and microcracks are observed. However, this process is reversed on discharge, removing all traces of the microcracking. The authors developed a diffusion-induced stress model to understand the origin of the planar gliding and propose ways to stabilize these nickel-rich cathodes in working batteries. Science , this issue p. 1313 Reversible gliding and microcracking of lattice planes are observed in single-crystalline Ni-rich cathode materials. High-energy nickel (Ni)–rich cathode will play a key role in advanced lithium (Li)–ion batteries, but it suffers from moisture sensitivity, side reactions, and gas generation. Single-crystalline Ni-rich cathode has a great potential to address the challenges present in its polycrystalline counterpart by reducing phase boundaries and materials surfaces. However, synthesis of high-performance single-crystalline Ni-rich cathode is very challenging, notwithstanding a fundamental linkage between overpotential, microstructure, and electrochemical behaviors in single-crystalline Ni-rich cathodes. We observe reversible planar gliding and microcracking along the (003) plane in a single-crystalline Ni-rich cathode. The reversible formation of microstructure defects is correlated with the localized stresses induced by a concentration gradient of Li atoms in the lattice, providing clues to mitigate particle fracture from synthesis modifications.